2021
DOI: 10.3390/pathogens10010080
|View full text |Cite
|
Sign up to set email alerts
|

Current Arboviral Threats and Their Potential Vectors in Thailand

Abstract: Arthropod-borne viral diseases (arboviruses) are a public-health concern in many regions of the world, including Thailand. This review describes the potential vectors and important human and/or veterinary arboviruses in Thailand. The medically important arboviruses affect humans, while veterinary arboviruses affect livestock and the economy. The main vectors described are mosquitoes, but other arthropods have been reported. Important mosquito-borne arboviruses are transmitted mainly by members of the genus Aed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Culex quinquefasciatus is a primary vector of lymphatic filariasis disease, which has caused serious negative social, economic, and health impacts in tropical and subtropical countries [ 38 ]. A report in Thailand revealed that this mosquito species is able to transmit several other medically important pathogens, such as Japanese encephalitis, West Nile virus, Zika virus, and Tembusu virus [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Culex quinquefasciatus is a primary vector of lymphatic filariasis disease, which has caused serious negative social, economic, and health impacts in tropical and subtropical countries [ 38 ]. A report in Thailand revealed that this mosquito species is able to transmit several other medically important pathogens, such as Japanese encephalitis, West Nile virus, Zika virus, and Tembusu virus [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Around 1000 species of sandflies have been identified with the arbovirus-relevant species found within two genera: Phlebotomus and Lutzomyia [63]. Although more commonly vectors for parasitic diseases like Leishmaniasis, infected female sandflies can transmit phleboviruses during blood feeding, and cases are often found clustered geographically during an outbreak [64].…”
Section: Sandfliesmentioning
confidence: 99%
“…Arthropod-borne or arbovirus diseases are public-health concerns in many regions of the world, including Thailand. Important mosquito-borne diseases affecting humans in Thailand include dengue, chikungunya and Zika [Raksakoon & Potiwat, 2021]. However, there are currently no safe and highly effective vaccines available for preventing these diseases [Huang et al, 2023; Costa et al, 2021].…”
Section: Introductionmentioning
confidence: 99%